Association between levels of thiamine intake, diabetes, cardiovascular diseases and depression in Korea: a national cross-sectional study. (27th April 2021) - Duc, Hai Nguyen; Oh, Hojin; Yoon, In Mo; Kim, Min-Sun
Abstract: The present study aimed to determine thiamine intake levels and the association between thiamine intake, diabetes, cardiovascular diseases and mental health. Participants were interviewed to obtain data on socio-demographic characteristics, lifestyle, current medications, medical and family history. The daily intake of thiamine was assessed by a 24-h recall. The mean age of the 34 700 study subjects was 42⋅9 years (sd 22⋅8, min–max: 1–80) and 19 342 (55⋅7 %) were women. The levels of thiamine intake were 1⋅126 mg (2016), 1⋅115 mg (2017) and 1⋅087 mg (2018) for women, which were equal to or only slightly above the recommended intake of 1⋅10 mg/d for women. The levels of thiamine intake from 2014–15 and 2016–18 significantly decreased. The estimated percentage of insufficient thiamine intake was 37⋅8 % (95 % CI 37⋅3, 38⋅4). Multivariable regression analysis adjusted for potential confounders showed that thiamine intake was critically associated with lower risks of hypertension, MI or angina, type 2 diabetes, depression and dyslipidemia. The daily thiamine intake from food can reversal the risks of hypertension (OR 0⋅95; 95 % CI 0⋅90, 0⋅99), MI or angina (OR 0⋅84; 95 % CI 0⋅74, 0⋅95), type 2 diabetes (OR 0⋅86; 95 % CI 0⋅81, 0⋅93), depression (OR 0⋅90; 95 % CI 0⋅83, 0⋅97) and dyslipidemia (OR 0⋅90; 95 % CI 0⋅86, 0⋅95), respectively. Further works are needed to identify the effects of thiamine and non-communicable diseases (NCDs) and mental health. A preventive thiamine supplementation strategy should be adopted to target NCDs and mental health and risk factors associated with thiamine deficiency. The optimisation of NCD control and mental health protection is also a vital integral part of Korea's public health system.